Morphometric Study and Toxicity Assessment for Horseshoe Crab Collected From Kampung Pasir Putih, Sarawak, Malaysia - Er, Huey Hui (Universiti Malaysia Sarawak (UNIMAS), 2015)
In Malaysia, horseshoe crabs encountered the decreases in population, which might due to the anthropogenic factor. Hence, this study was carried out to study the morphometric characteristic and to assess the toxicity of horseshoe crabs collected by local fishermen at 2014 and 2015 from Kampung Pasir Putih, Sarawak, Malaysia. The morphometric and allometric analysis was used to study the morphometric variability between the sexes of horseshoe crabs. All the samples collected were confirmed to be Tachypleus gigas. The body weight of both sex had increased at 2015 as compared to 2014. All parameters in females were recorded high especially body weight as compared to the males. The mean body weight of females were 787.22±93.73 g and males were 298.71±29.58 g. Allometric analysis shown that the specimens collected for both sexes have a high degree of correlation between total length and body weight. However, the b values (female=0.1813; male=0.1961) shown a negative allometric growth characteristic. Due to the frequent occurrence of food poisoning after consuming horseshoe crab, toxicity analysis was carried out in this study. For toxin analyses, thin layer chromatography, high performance liquid chromatography, and liquid chromatography mass spectrometer were performed. TLC was used as a screening for TTX, HPLC was to confirm for the presence of TTX and LCMS/MS was used to quantify the amount of TTX presence. TTX was most frequent detected in the eggs with the toxicity range from 3.53 MU/g to 6.5 MU/g. In viscera caecum and soft tissue, the toxic amount range from 1.22 MU/g to 6.81 MU/g and 1.96 MU/g to 6.15 MU/g respectively. This study was inferred that the horseshoe crab T. gigas collected are non-toxic (less than 10 MU) and safe to be consumed.